STUDI KOMPARASI PEMODELAN INVERSI 1-D, 2-D, DAN 3-D DATA MAGNETOTELLURIK DI DAERAH PANAS BUMI LOKOP, PROVINSI ACEH: COMPARATIVE STUDY OF MAGNETOTELLURIC 1-D, 2-D, AND 3-D INVERSION MODELLING AT LOKOP GEOTHERMAL AREA, PROVINCE OF ACEH - Wiwid Joni; Iqbal Takodama (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
Magnetotelluric (MT) method can determine conductivity structure in geothermal area which could be interpretated as smectite clay (clay cap) is commonly used to help target geothermal wells and assess resource capacity. In order to process MT data, we can do 1-D, 2-D, and 3-D inversion modelling to produce a realistic MT model data. 1-D inversion is very easy to do, where this model can support an effective quality assurance of each MT station data. 1-D inversion is usually able to characterize the overall resistivity geometry of a geothermal clay cap, although not abrupt edges or deep variations. In order overcome this uncertainty, 2-D inversion can be performed. However, 2-D inversion can't work properly if our MT survey in complicated geological environments.The limitations of 1-D and 2-D inversions can be fixed by performing 3-D inversion. The modelling application was carried out using MT data in Lokop geothermal area, Province of Aceh.1-D and 3-D modeling result can better describe the possibility of clay cap in Lokop geothermal area.